2016
DOI: 10.1016/j.pmedr.2016.06.010
|View full text |Cite
|
Sign up to set email alerts
|

Ethnicity, socioeconomic status, and overweight in Asian American adolescents

Abstract: Asian American children and adolescents are an under-investigated subpopulation in obesity research. This study aimed to identify specific profiles of Asian subgroups at high risk of adolescent overweight with special attention to Asian ethnicity, socioeconomic status (SES), and their interaction. Multiple logistic regression models were fitted using a sample of 1533 Asian American adolescents ages 12–17 from the 2007–2012 California Health Interview Survey (CHIS). In addition to Asian ethnicity and socioecono… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

3
26
1

Year Published

2017
2017
2024
2024

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 21 publications
(30 citation statements)
references
References 50 publications
3
26
1
Order By: Relevance
“…We acknowledge the limited attention to the diversity within each ethnic group as a limitation. Here, findings of a prior study (Cook et al, 2016) are worth noting as they shed some light on this. Using interaction terms between low individual income and Asian ethnicities, this study found greatly-elevated odds of being overweight in Southeast Asian and Vietnamese adolescents (i.e.…”
Section: Discussionmentioning
confidence: 70%
See 2 more Smart Citations
“…We acknowledge the limited attention to the diversity within each ethnic group as a limitation. Here, findings of a prior study (Cook et al, 2016) are worth noting as they shed some light on this. Using interaction terms between low individual income and Asian ethnicities, this study found greatly-elevated odds of being overweight in Southeast Asian and Vietnamese adolescents (i.e.…”
Section: Discussionmentioning
confidence: 70%
“…those in the low-SES ethnic groups) who also had low family incomes. Somewhat akin to the interaction between individual- and neighborhood level disadvantage, characterized as the “double jeopardy” in past research (Wen & Christakis, 2005), these findings suggest that the adverse effects of disadvantage on the ethnic group level on adolescent overweight/obesity may be further intensified for those who also experience individual-level poverty (Cook et al, 2016). Further research attention to these disadvantaged Asian subgroups is warranted to address health disparities disproportionately affecting them.…”
Section: Discussionmentioning
confidence: 79%
See 1 more Smart Citation
“…Association between maternal nativity and maternal time in the US and obesity among Asian American children ages 2 to 11 years old (n = 609): CHIS 2013-2016. 3 odds ratio, 4 adjusted odds ratio (controlling for family income), 5 confidence interval, * p < 0.05.…”
Section: Maternal Nativitymentioning
confidence: 99%
“…While the prevalence of overweight/obesity is relatively low in this population compared to other racial/ethnic groups [1][2][3], there is a need to better understand risk factors for elevated body mass index (BMI) in Asian American children for several reasons. First, some Asian American ethnic subgroups have a higher prevalence of overweight/obesity than others [4][5][6][7]. One study found that Filipino and Vietnamese American children are more likely to have elevated BMI than their white peers [7].…”
Section: Introductionmentioning
confidence: 99%